Unveiling Organizational Impact on Civil Servant’s Change Readiness: Investigating the Mediating Influence of Adaptability - Iswandari, Virginia Dewi; Pusparini, Elok Savitri (Jurnal Administrasi Publik (Public Administration Journal), 2023)
Employees’ response to organizational change remains pivotal in determining the success of change initiatives, especially within public sector organizations. This study aims to explore the determinants of change readiness among civil servants. Data was gathered through surveys of 350 civil servants involved in organizational change processes. Various factors influencing change readiness were identified, and their direct impact was assessed. Furthermore, the study delved into the mediating role of adaptability in the relationship between these factors and change readiness. Results indicate that organizational identification exerts a positive yet statistically insignificant influence on employees’ change readiness, while managerial climate significantly impacts employees’ change readiness. Adaptability emerged as a mediator between these factors and employees’ change readiness. This research contributes to understanding the determinants of employees’ adaptability and change readiness, offering valuable insights into human resources management and organizational development.